Construção da sonoridade do coro amador: estratégias utilizadas por regentes - Silva, Ana Paula Guimarães (2018)
Introduction: in considering that 90% of the choirs in the world are amateurs and that most of the time they do not receive guidance from a vocal coach, in most cases, only the conductor is responsible for the vocal preparation of the choristers and the attribution of a collective sound. Objective: to verify the strategies used by a group of amateur choir conductors to construct the sonorities of their choirs. Method: This is a descriptive cross-sectional observational study. A survey was prepared for the study based on the literature and the experience of the researchers, divided into three parts: identification and characterization of the sample, characterization of the analyzed amateur choir and investigation on the choral sonority. The selection of the subjects was given by the snowball technique and the inclusion criteria was to be at least 18 years older, to be regent of amateur choir with minimum experience of two years and to be ruling the group for at least six months. For the answers on the form of work with the sonority were created five categories with the most recurrent terms. A descriptive statistical analysis was performed using absolute and relative frequencies. Results: the sample was finalized with 65 regents, 58.5% male and 41.5% female, with a mean age of 42.2 years and 64.6% of them had ten or more years of career. About the characteristic of the amateur choir, the majority were popular music (70.8%), with 10 to 20 members (38.5%) and age group between 31 to 40 years old (30.8%). In the construction of the sonority, the category of technical aspects was highlighted, with 42.4%, followed by tunes with 19.2% aspects related to the interpretation and aspects of musical perception, and lastly, aspects related to body / breathing with 10.1%. The majority (70.8%) of the regents reported difficulties to achieve the desired sonority. Conclusion: the group of regents analyzed used as strategies to work sound mainly technical aspects: vocalizes; vocal technique; warm-ups and resonance